A metamodern model for managing stakeholder relationships in non-profit organisations - Irma Meyer; Rachel Barker (Communicare)
It is posited that this article is an important theoretical addition in the field of strategic communication as it seeks to eradicate the conceptual tension between the two dominant discourses, namely modernist and postmodernist explanations of how organisations should manage stakeholder relationships. Modernists believe in a single truth, accept metanarratives and believe that grand theory represents knowledge and can explain everything, whilst postmodernists reject the absolute standards and grand theories typical of modernism in favour of awareness and tolerance of differences, ambiguity and conflict. This article links these two perspectives in a new metamodern model for stakeholder relationship management, aimed specifically at the South African non-profit sector. A conceptual theoretical framework was developed and tested by means of exploratory qualitative and interpretative research through interviews with senior management in the non-profit sector. The findings suggest that a metamodern perspective requires constant negotiation between modernism and postmodernism. We also highlight the need for formal training in stakeholder relationship management. This entails adopting a micro-perspective by regularly identifying current strategic issues, mapping the stakeholders involved and linking them to these issues, and designing focused communication strategies to manage stakeholder relationships. The main research implications are that stakeholder relationship management is a function which should not simply be delegated to the communication specialist, and that it should be practised from a metamodern perspective and not a modernistic or postmodern perspective. The originality and value of this research initiative lies in the development of a metamodern model for stakeholder relationship management for the non-profit sector which has been proposed and tested in practice.